Dolomite microstructures between 390° and 700 °C: Indications for deformation mechanisms and grain size evolution. (August 2016) - Berger, Alfons; Ebert, Andreas; Ramseyer, Karl; Gnos, Edwin; Decrouez, Danielle
Abstract: Dolomitic marble on the island of Naxos was deformed at variable temperatures ranging from 390 °C to >700 °C. Microstructural investigations indicate two end-member of deformation mechanisms: (1) Diffusion creep processes associated with small grain sizes and weak or no CPO (c rystallographicp referredo rientation), whereas (2) dislocation creep processes are related with larger grain sizes and strong CPO. The change between these mechanisms depends on grain size and temperature. Therefore, sample with dislocation and diffusion creep microstructures and CPO occur at intermediate temperatures in relative pure dolomite samples. The measured dolomite grain size ranges from 3 to 940 μm. Grain sizes at Tmax >450 °C show an Arrhenius type evolution reflecting the stabilized grain size in deformed and relative pure dolomite. The stabilized grain size is five times smaller than that of calcite at the same temperature and shows the same Arrhenius-type evolution. In addition, the effect of second phase particle influences the grain size evolution, comparable with calcite. Calcite/dolomite mixtures are also characterized by the same difference in grain size, but recrystallization mechanism including chemical recrystallization induced by deformation may contribute to apparent non-temperature equilibrated Mg-content in calcite. Highlights: Dolomite grain size shows Arrhenius type relationship to inferred temperatures. Dolomite grain size is five times smaller as of calcite in the same locality. Dislocation creep in dolomite dominates from ∼500 °C and grain size ∼100 μm onward. Dolomite/Calcite mixtures show common recrystallization process influencing each other.